Eye tracking measurement with headrest in reading aloud study - Daman, Nadira Syahira; Che Azemin, Mohd Zulfaezal; Taib, Ibrahim Adham; Ahmad, Norsham (Management & Science University (MSU), 2019)
Eye tracking is a technology used to track and record what the human eye perceives. It has been applied in detecting visual field loss, determining infant’s preferential looking and virtual reality therapy. In reading tasks, eye tracking needs to be accurate because even a substantial head movement can affect its fixation accuracy; as such, using a headrest can minimise head movements and the associated fixation errors. This experimental study was conducted to determine the effect of headrest usage on eye tracker fixation accuracy during reading aloud activity by comparing a group with headrest and a group without it. The results showed that the difference between the two groups was significant (p=0.004), where the headrest group and non-headrest group introduced a mean fixation error of 30.728 ± 15 mm and 17.671 ± 9 mm respectively. Eye tracking accuracy for the headrest group was then compared with a standard value of 0.6 degrees. The findings showed that the accuracy was significantly different (p<0.001) from the standard value, with a mean of 3.513 ± 1.700 degrees. In conclusion, headrest usage does not increase eye tracking accuracy in reading aloud activity.